Pemanfaatan Teknologi Web dalam Pengembangan Sistem Informasi Sekolah untuk Meningkatkan Layanan Publik di SD Negeri 1 Demung Besuki, Situbondo - Muafi Muafi; Muh. Ilham Fahmi; Narendra Yogi Prasetyo; Dwi Candra Aldianto (Jurnal Kridatama Sains dan Teknologi, 2026)
Digital transformation in the basic education sector has become an urgent necessity in the era of information technology. SD Negeri 1 Demung Besuki, Situbondo, as an educational institution, has not yet implemented an integrated information system to manage public services such as academic information, the school profile, and communication with parents. The school still relies on manual methods that may lead to inefficiency and delays in delivering information. This study aims to design and implement a web-based school information system to improve the quality of public services through technology integration. This research adopted the waterfall method, consisting of the following stages: requirements analysis (field observations and interviews with stakeholders, including the principal, teachers, and parents), system design (relational database design, process flow design, and user interface design), system implementation, and testing and evaluation. Functional testing was conducted using black-box testing, while usability was evaluated using the System Usability Scale (SUS) questionnaire. The developed system provides core school information services, including dynamic content management (school profile, news, and gallery), a real-time announcement module, and an admin dashboard for updating information, with a responsive interface compatible with mobile devices. The evaluation results indicate a 72% improvement in information delivery efficiency, calculated by comparing the average efficiency indicator scores (e.g., speed of accessing information, timeliness of receiving announcements, and reduced need for manual confirmations) before and after the system implementation, based on questionnaire data from participants consisting of teachers/parents. Therefore, the web-based school information system contributes significantly to faster and more efficient public service delivery compared to conventional methods